THE EFFECT OF TRADE INTERMEDIARIES ON COST STRUCTURE AND PRODUCT PRICES IN THE DOMESTIC MARKET - Bagus Tri Prasetyo; Galih Sakti Kurniawan; Salsabila Halena Diah; Muchammad Zoga Nur Aprianto; Rodhatun Nimah (CV KULTURA DIGITAL MEDIA, 2026)
Trade intermediaries play an important role in the domestic distribution system by bridging the relationship between producers and consumers. Their presence is expected to enhance distribution efficiency by reducing transaction costs; however, in practice, intermediaries are often associated with higher cost structures and increased product prices. This study aims to analyze the influence of trade intermediaries on distribution cost structures and product price formation in the domestic market. The research employs a qualitative-descriptive approach using a literature review method, drawing on academic journals, economics textbooks, and other relevant sources. The findings indicate that trade intermediaries have a dual role: they can serve as a source of efficiency through functional specialization in distribution, but they may also become a source of inefficiency when operating in highly concentrated market structures. The length of the distribution chain contributes significantly to cost accumulation and price disparities between producer and consumer levels. In the Indonesian domestic market context, the dependence of small producers on intermediaries strengthens the bargaining power of intermediaries and affects price structures. Therefore, public policies should focus not only on reducing the number of intermediaries but also on improving efficiency, transparency, and fair competition within the distribution system to enhance overall economic welfare.